2005
DOI: 10.1210/jc.2004-2268
|View full text |Cite
|
Sign up to set email alerts
|

A Common Single Nucleotide Polymorphism in Exon 10 of the Human Follicle Stimulating Hormone Receptor Is a Major Determinant of Length and Hormonal Dynamics of the Menstrual Cycle

Abstract: The FSH receptor Ser680/Ser680 genotype is associated with higher ovarian threshold to FSH, decreased negative feedback of luteal secretion to the pituitary during the intercycle transition, and longer menstrual cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
6
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 32 publications
6
97
6
3
Order By: Relevance
“…In females, these SNPs have been shown to influence serum FSH levels during the follicular phase of the menstrual cycle [42]. Our results indicated that there was no association between these SNPs and the mean value of baseline FSH, which was a result inconsistent with the findings of Sudo et al [16], and also, we found no association between 307 and 680 SNPs and the mean value of LH, E2, and PRL levels in infertile women.…”
Section: Discussioncontrasting
confidence: 93%
“…In females, these SNPs have been shown to influence serum FSH levels during the follicular phase of the menstrual cycle [42]. Our results indicated that there was no association between these SNPs and the mean value of baseline FSH, which was a result inconsistent with the findings of Sudo et al [16], and also, we found no association between 307 and 680 SNPs and the mean value of LH, E2, and PRL levels in infertile women.…”
Section: Discussioncontrasting
confidence: 93%
“…27,28 Nakamura et al 13 reported on a patient with primary amenorrhea but normal sized ovaries containing some small antral follicles. These follicles reacted to high doses of hMG injection.…”
Section: Discussionmentioning
confidence: 99%
“…G −29 A, A 919 G (Thr 307 Ala) and A 2039 G (Asn 680 Ser) polymorphisms have been extensively studied by different investigators. It was reported that the polymorphism A 2039 G is associated with high basal FSH levels in women undergoing Assisted Reproductive Technology (ART) programme [17][18][19][20][21][22]. Recently, we have reported association of FSHR gene polymorphism (A 919 G, G −29 A) with altered ovarian response in subjects undergoing gonadotropin treatment during ART programme [23,24].…”
Section: Introductionmentioning
confidence: 94%
“…Primary amenorrhea subjects (n=48) Secondary amenorrhea subjects (n=38) response of the ovary to exogenous FSH [17,18,20,22]. However, a few studies have refuted this view [22,33].…”
Section: Hormonementioning
confidence: 99%
See 1 more Smart Citation